Municipal awareness as an integral part for enhancing citizen satisfaction of Malaysian municipal councils, Batu Pahat - Kasim, Rozilah; Bello, Muhammad Umar; Martin, David (Path of Science, 2017)
This research study critically analysed the existing literature on municipal awareness relevancy of municipal councils’ service delivery for the purpose of enhancing citizen satisfaction. The purpose of the study is the investigation of citizen satisfaction level of municipal services through the use of municipal awareness. The Material and methods were carried out using secondary data and were meticulously and critically analysed to come up with reliable results. The study shows the relevance of the public awareness, citizen satisfaction and municipal council performance in Malaysia. It is evidence in the research that citizen consent is important before municipal services should be provided in the local community. The research study highlighted many discrepancies in many kinds of literature related to the existing research study, evidence-based analysis were carried out to buttress importance and significance of the related study to the research work. The literature was reviewed to ascertain the current happening in the area of municipal council service delivery. The study shows that many municipal councils in Malaysia provide adequate and satisfactory services to their citizens’. The results of the study also revealed that municipal awareness plays an important role on citizen satisfactions of municipal service delivery. It is also evident that adequate provision of services has direct bearing with municipal councils. The study concludes that municipal service delivery can be enhanced through citizen awareness campaign, to sensitise the local community on various aspects of service delivery including maintenance of the facilities provided. The study also concludes that local Authorities lack of awareness section affects their performance in service delivery process. The study recommends that municipal councils need to consults the citizen for their needs and wants; awareness campaign needs to be regularly carried out to maintain cordial relationship between local Authorities and their citizen; it is also recommended that municipal services should be delivered the needed services by the local inhabitants’ after duly consultation.